Infrastructure Classification Revisited - Momoh, Mohammed Aliu (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The impact infrastructure has long been viewed as a key ingredient for economic development. Though it has a strong growth promoting, the enormous need and complexity of infrastructure has made it difficult to define. The infrastructure definition and classification debate has been on for decades. Scholars have argued that and viewed the issue of definition and classification from different perspective ranging from aggregation to the need to reconcile the analytic and not necessarily compatible objectives. This paper reconciles the issues around the description and classification of infrastructure. It examined the various classification overtime, taking cognizance of the issues of appropriate description to meet policy challenges.